Pertanggungjawaban Pidana Terhadap Anak Sebagai Pelaku Tindak Pidana Narkotika Dengan Menerapkan Restorative Justice Melalui Diversi : Studi Penetapan Nomor 4/Pid.Sus-Anak/2017/PN.Mdn dan Penetapan Nomor 31/Pid.Sus-Anak/2017/PN.Mdn - Saddam Yafizham Lubis; Syafruddin Kalo; Marlina Marlina; Edy Ikhsan (Universitas Sumatera Utara, 2019)
Abstract. Facing and overcoming various crimes and behavior of children in the context of efforts to foster and protect children which is an important factor, the alternative punishment that can be used is to apply punishment with the concept of restorative justice through diversion. Which aims so that children can improve themselves and the interests of children when they are faced with the law. The main concern of the concept of diversion and restorative justice is the interests of the perpetrators, victims, families of victims/perpetrators, and the community. Settlement of cases by applying restorative justice through diversion in Determination Number 4/Pid.Sus-Anak/2017/PN.Mdn and Determination Number 31/Pid.Sus-Anak/2017/PN.Mdn, wherein the two stipulations the child is charged with acts narcotics criminal. The type of research used is normative legal research that refers to legal norms contained in the legislation and court decisions. The analysis in this study is qualitative analysis by drawing conclusions deductively, namely drawing conclusions from things that are general to things of a special nature. From the results of the study, it is known in the Determination Number 4/Pid.Sus-Anak/2017/PN.Mdn and Determination of Number 31/Pid.Sus-Anak/2017/PN.Mdn states that children as narcotics criminals are solved through diversion. That the achievement of agreement/deliberation through diversion has been carried out and stipulates the termination of criminal cases by conducting rehabilitation, returning to parents, and continuing school. Keywords : criminal responsibility, narcotics crime, diversion, and restorative justice